Physiological super-resolution in situ recording reveals kinetic changes of sympathetic norepinephrine release in heart failure - Bing Liu; Xiaohan Jiang; Shu Guo; Xinjiang Kang; Jing Lu; Shirong Wang; Wei Yao; Xianhong Ou; Jing Yan; Tian Li; Jingli Gu; Yun Xiu; et al. (Proceedings of the National Academy of Sciences, 2026)
Norepinephrine (NE) in the peripheral nervous system plays crucial roles in regulating peripheral organs in health and disease. However, the spatiotemporal dynamics of sympathetic NE release and its underlying mechanisms remain poorly characterized due to technical challenges. Here, we developed and validated a Slice ElectroChemistry (SEC) method to record sympathetic NE release in heart slices with combined super-resolution and high sensitivity at 1 μm × 1 ms × 1 nM as in patch-clamp recordings. By using the SEC method, we revealed the increased NE release, impaired NE reuptake, increased releasable NE-vesicle pool, and impaired vesicle recycling of sympathetic nerves in the heart of transverse aortic constriction-induced heart failure (HF) mouse model, and defined the increased expression of Cav2.2 calcium channel as a central mechanism mediating the facilitation of NE release and thus the pathogenesis of HF, clarifying a longstanding puzzle about the kinetic changes of cardiac sympathetic NE release in HF. Beyond the heart, SEC enables NE release recording in other peripheral organs and human tissues, providing a robust toolset to investigate sympathetic NE dynamics across diverse pathophysiological conditions.